2018
DOI: 10.2139/ssrn.3253613
|View full text |Cite
|
Sign up to set email alerts
|

Identifying People in Poverty: A Multidimensional Deprivation Measure for the EU

Abstract: In this article, I propose a multidimensional deprivation measure of poverty for the EU. The paper stands on the claim that a deprivation measure can be adequate, both conceptually and empirically, to capture poverty in the EU defined in Townsendian terms. Yet existing deprivation scales have three conceptual problems such as data-driven specification, neglected dimensionality and missing dimensions, and four data problems such as limited extent, cross-cultural equivalization, behavioral choices and reporting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…Most directly, Tomlinson et al's work has been critically evaluated by Webb (2019), who repeated the analysis with recent data and more sophisticated analytic techniques to conclude its continued validity with the provisos that low life satisfaction emerges as a distinct dimension while social isolation does not, possibly due to measures that confound isolation with social exclusion. Bedük's (2018) analysis of poverty in 29 European countries, in contrast, postulated and found that limited ability to engage in social relationships and leisure was confirmed as one of four dimensions 6 alongside lack of basic needs, 'habitancy' (precarious housing circumstances) and inability to afford health promoting services and behaviour.…”
Section: Poverty: On the Idea Of Multidimensionalitymentioning
confidence: 99%
“…Most directly, Tomlinson et al's work has been critically evaluated by Webb (2019), who repeated the analysis with recent data and more sophisticated analytic techniques to conclude its continued validity with the provisos that low life satisfaction emerges as a distinct dimension while social isolation does not, possibly due to measures that confound isolation with social exclusion. Bedük's (2018) analysis of poverty in 29 European countries, in contrast, postulated and found that limited ability to engage in social relationships and leisure was confirmed as one of four dimensions 6 alongside lack of basic needs, 'habitancy' (precarious housing circumstances) and inability to afford health promoting services and behaviour.…”
Section: Poverty: On the Idea Of Multidimensionalitymentioning
confidence: 99%